1997
DOI: 10.2307/3284224
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin and Ecdysteroid Titers in Ixodes scapularis during Vitellogenesis

Abstract: Ecdysteroids are the only hormones unequivocally identified thus far in ticks. We found a positive correlation between ecdysteroid concentration and vitellogenin synthesis in female Ixodes scapularis. Vitellogenin (Vg) synthetic activity was measured by an in vitro assay for Vg, involving incubations of the fat body with 35S-methionine and immunoprecipitation collected on a solid-phase matrix, protein A. Vitellogenin synthetic activity in the fat body was undetectable in unfed females but was detected after ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…azedarach , showing that this plant interferes with the neuroendocrine system of insects (Schmidt et al ., 1998). Although the physiology of reproduction in ticks is not as well understood as in insects, the participation of ecdysteroids in this process has been demonstrated (James et al ., 1997). Therefore, the reproductive effects observed on B. microplus females are probably due to alterations on the neuroendocrine system of the tick.…”
Section: Means ± Sd Of Mortality Rates Of Boophilus Microplus Larvae mentioning
confidence: 99%
“…azedarach , showing that this plant interferes with the neuroendocrine system of insects (Schmidt et al ., 1998). Although the physiology of reproduction in ticks is not as well understood as in insects, the participation of ecdysteroids in this process has been demonstrated (James et al ., 1997). Therefore, the reproductive effects observed on B. microplus females are probably due to alterations on the neuroendocrine system of the tick.…”
Section: Means ± Sd Of Mortality Rates Of Boophilus Microplus Larvae mentioning
confidence: 99%
“…Glucose is the primary carbohydrate constituent in mammalian blood [26], [27] and B. burgdorferi can use glucose to support growth [28]. Ticks rely on a high concentration of carbohydrates and other nutrients available in the blood meal for molting and successful oogenesis [29], [30]. During feeding, ticks create a peritrophic matrix above the epithelial cell layer, which serves both as a compartment to trap the blood meal and as a barrier to prevent invasion by microorganisms that accompany the blood meal.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified ecdysteroids in ticks and mites using various detection methods. Ecdysone and 20E were identified by high performance liquid chromatography (HPLC)-radioimmunoassay in the hard tick Ixodes scapularis during the vitellogenic period (James et al, 1997). They were also identified in the soft tick Ornithodoros parkeri and the final hydroxylation from ecdysone to 20HE occurred in epidermal tissues (Zhu et al, 1991).…”
Section: Introductionmentioning
confidence: 99%